Proses Pembubutan Rata Bahan AISI 1010 Dengan Mesin CNC Untuk Mendapatkan Kualitas Permukaan Yang Optimum - Bena Aldi Finandika; Joko Waluyo*; Prabuditya Bisma (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
Surface quality is one of the most important things in turning machining process. The use of the right turning parameters can produce optimal surface quality. The parameters used in this flat turning CNC turning process are AISI 1010 steel using three revolutions at the spindle rotation, namely 1989, 2089, and 2188 revolutions per minute and the selected feeding is 0.1 mm/put, 0.15 mm/put, and 0.25 mm. /put and feed depth of 1.0, 1.5, and 2.0 mm. The optimal price can be obtained for each parameter using Taguchi method. Surface roughness was measured after the flat turning process, and then analysis of variance (ANOVA) and signal to noise ratio analysis were carried out according to Taguchi's design proposal. The results obtained from the analysis of variance, the feed rate parameter was identified as having a large effect on surface roughness at a contribution of 73,10.%, then spindle rotation at a contribution of 17.50% and infeed depth at a contribution of 7,30%. The results of the signal to noise ratio analysis to obtain the best parameters for surface roughness are at spindle rotation of 2188 rpm, feed rate 0.15 mm/put, and feed depth of 1.0 mm with an average surface roughness of 0.804 µm.